The Effect of Implementing an Internal Control System, Implementing Information Technology and Human Resource Competence on the Quality of Financial Reporting (Study of South Aceh Regional Work Unit) - Julisa, T. Rahmad; Arfan, Muhammad; BZ, Fazli Syam (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research seeks to examine how the adoption of an internal control system, the use of information technology, and the competence of human resources impact the quality of financial reporting in the South Aceh District Working Unit (SKPK). The research population included 37 SKPKs, with 111 questionnaires distributed to the Head of SKPK, Expenditure Treasurer, and Financial Administration Officers (PPK-SKPK). The data was analyzed using multiple linear regression with SPSS software. The findings reveal that the implementation of internal control systems, information technology, and human resource competencies has an impact on the quality of financial reporting. Furthermore, both the individual implementation of internal control systems and information technology positively influence the quality of financial reporting.